As análises do tempo de Wittgenstein e o argumento da linguagem privada: o fim da memória como parte da estrutura lógica do mundo - Silva, Guilherme Ghisoni da (Universidade Federal de São Carlos, 2011)
The aim of this thesis is the study of Wittgenstein s analyses of time, during the middle period, and the connections of those analyses to the private language argument. This study showed the importance granted to memory, in 1929-1930, which allowed using it as a key concept for the understanding of a major change that happened to Wittgenstein s philosophy in the early thirties (the abandonment of the thesis of the complete determination of sense). The understanding of this abandonment, through the perspective of the analyses of time, taking memory as a key concept, was used as a backdrop for the comprehension of some important passages from the book Philosophical Investigations, in which Wittgenstein deals with the problem of the language of sense-data and private experience.
Keywords: Wittgenstein, Ludwig Josef Johann, 1889-1951; Tempo (Filosofia); Memória; Fenomenologia; Linguagem privada; Memory; Time; Phenomenology; Private experience; CIENCIAS HUMANAS::FILOSOFIA